Medical Journal of Indonesia Vol.24. Issue 4, December 2015 pp 195-261 - Redaksi (FK Universitas Indonesia, 2015)
- Phylogenetic analysis and predicted functional effect of protein mutations of E6 and E7 hpv16 strains isolated in Indonesia - Clinical symptoms and related factors of obstructive sleep apnea among overweight and obese taxi drivers - Steroid response as prognostic factor and its correlation with molecular assessment of childhood acute lymphoblastic leukemia -...